A bioinformatician's guide to the forefront of suffix array construction algorithms - Shrestha, A. M. S.; Frith, M. C.; Horton, P. (Briefings in bioinformatics, 2014)
The suffix array and its variants are text-indexing data structures that have become indispensable in the field of bioinformatics. With the uninitiated in mind, we provide an accessible exposition of the SA-IS algorithm, which is the state of the art in suffix array construction. We also describe DisLex, a technique that allows standard suffix array construction algorithms to create modified suffix arrays designed to enable a simple form of inexact matching needed to support 'spaced seeds' and 'subset seeds' used in many biological applications.